Chemical cellulation technique for lightweight clay bricks - Razak, H.A.; Mahde, A.K.; Yahya, A.H. (2002)
Lightweight clay bricks were produced using a chemical cellulation technique from a residual soil of high clay content, mostly non-crystalling. The cellulation technique introduces cells into the material during the mixing stage as a result of the chemical reaction between aluminium powder and quicklime, which liberates hydrogen gas. The technique also requires the use of sodium silicate to achieve a proper cellulated structure. The mechanisms of reaction of the abovementioned chemicals with each other as well as with the raw material were investigated. Engineering properties of the fired product, namely compressive strength, bulk density, water absorption, and volumetric shrinkage, were determined and compared with solid bricks prepared in the laboratory. Based on the results of the study, a mechanism for the cellulation process, though complex, is postulated. The process is a combination of chemical reaction between the chemical additives used and the response of the soil to the chemicals or to the reaction products. The study also reveals the possibility of producing lightweight clay bricks, mostly of loadbearing performance, using the residual soil.